Status and contamination rate of informal wheat seeds to seed-born diseases in Golestan province - صمد مبصر; لیلا زارع; مهرناز مهرآور (علوم و فناوری بذر ایران, 2012)
An investigation to show importance of contamination of informal wheat seed to seed-borne diseases were conducted in Golestan Province. In 2007, a field survey was conducted in growing wheat fields using informal seed for planting in 6 towns of Golestan Province as Aliabad, Aghghala, Gorgan, Kalaleh, Gonbad, and Fazelabad in order to identify the casual agent of seed-borne diseases on or in the seeds. Washing, deep freeze blotter, agar plate and embryo tests were used to isolate and identify the spores present on different part of the seeds. The results indicated 0.09- 45.55- 0.37- 66.19- 0.37- 0.17- 47.55- 0.12 -69.0 and 0.37 percent of Aliabad, Kalaleh, Gonbad, Gorgan, Aghghala, and Fazelabad seeds were infected by Ustilago tritici and Fusarium head blight, respectively. No seed samples was observed to be infected by Tilletia spp. spores in Golestan Province. Coefficient between Fusarium disease and factors involved in disease variablesare also studied. Continuously cultivation of wheat after corn causes an increase in Fusarium head blight, and nitrogen fertilizer application increases this disease. Micro-elements application can increase resistance ability of plant against these diseases